Investigation of Meander Delay System Properties using the „MicroWave Studio“ Software Package - Skudutis, J.; Daškevičius, V. (Elektronika ir Elektrotechnika, 2006)
Possibilities of applying the MicroWave Studio package to the investigation of properties of meander delay systems were analyzed. It is shown that properties of the delay system with meander electrodes shifted by half the period strongly depend on the distance between electrodes. If this distance is smaller than the gap between meander conductors, the system acquires properties which are not characteristic of symmetric meander systems. When the phase angle between adjacent conductor currents or voltages is θ =π/2 and when an integer number of half-waves of the non-retarded wave fits along the meander conductor, the influence of reflections on the meander delay system AFR is not revealed. The delay system with meander electrodes shifted by half the period has no pass-band (AFR break) at θ = π, and in the frequency range where the phase angle θ changes from 0 to π/2 the suppression is increased and the reflections are smaller. Ill. 12, bibl. 6 (in English, summaries in English, Russian and Lithuanian).